The predicative relative construction in Tsonga : (a descriptive study of its form and function) - Mayevu, George Shirhami (My University, 1978)
Refer to the document
Thesis (M.A. (African Languages)) --University of the North, 1978
Keywords: Tsonga language; Predictive relative clause construction; Grammar, Comparative and general -- Verb phrase; Tsonga literature; Tsonga language